1.)
a) 2√132:√11+14√30:(2√10)+9√21:√7-6*√3 =
b)(3√2-√5)*√3+√2*(√3-√20)+√5*(√3+√8)=
c) √48*(2√75-√27+2√27)-√48*√12=
d)√243*√147-2√3*7√3+3√8(5√72+6√128)=
2.)
a) (4√3+√32):4-(√8+√3)=
b) (2√32-10√14):(2√2)-(3√90-√3240):(3√5)=
c) (5√6-√96):√3-√48*(√24+4√6)=
d) (3√14-√350):√7-(2√486-√294):3


1

Răspunsuri

2014-08-05T00:09:43+03:00
1) a)2√12+ 7√3+9√3 -6√3=   2*2√3 +16√3 -6√3 =4√3 +16√3 -6√3= 14√3

b)3√6 -√15 +√6-√40+√15 +√40= 3√6+√6=4√6

c)4√3(2*5√3-3√3+2*3√3) -4√3 *2√3  =4√3(10√3-3√3+6√3) -8*3=4√3 *13√3 -24=

=52*3 -24= 156-24=132

d)√35721 -14*3 +3*2√2 *(5*6√2+6*8√2)   =189 -42 +6√2 *(30√2+48√2)=

=147 +6√2 * 78√2=  147 +468*2=  147 +936=  1083

2)a)(4√3 +4√2):4-2√2-√3=  √3 +√2 -2√2 -√3 = -√2

b)4-5√7 -√18+3√648=  -14 -5√7  -3√2 +3*18√2=  -14-5√7 -3√2 +54√2=

= -14-5√7 +51√2

c)5√2 -√32 -√1152-4√288=  5√2 -4√2 -24√2 -4*14√2=  -23√2- 56√2=  -79√2

d)3√2 -√50 -(2*9√6-7√6):3=  3√2 -5√2 -6√6 +7√6/3= -3√2 + (-18√6+7√6)/3=

= -3√2 -11√6/3